The Effect of Advertising Disclosure Language and Celebrity Endorsement on Tiktok on Purchasing Decisions for Fashion Outfit Products - Basem, Zamhir; Yulizar, Yulizar; Azhari, Azhari; Kamal, Mustafa; Ali, Auzar; Tetuko Barruansyah, Rauf (International Journal of Advanced Multidisciplinary, 2023)
This study aims to determine the effect of knowledge and capability on employee performance at PT. Ramajaya Pramukti Tapung, Kampar Regency. The population in this study were all employees at PT. Ramajaya Pramukti Tapung, Kampar Regency. The sample of this study used the technique of the census method so that the sample was all employees at PT. Ramajaya Pramukti Tapung Kampar Regency as many as 100 people. Data collection techniques used are questionnaires, observations and research files. The data analysis technique used is multiple linear regression analysis with a significant level (?) of 0.05. The results of this study conclude that Knowledge and Capability have a partially significant effect on employee performance, with a significant value less than 0.05. The results of the analysis of this study indicate that Knowledge and Capability have a significant simultaneous effect on employee performance at PT. Ramajaya Pramukti Tapung Kampar Regency. There is a very strong relationship between the independent variable and the dependent variable. The contribution of Knowledge and Capability variables to employee performance is 85.80%, which is very high.